A High‐Rate Electrode with Grotthuss Topochemistry for Membrane‐Free Decoupled Acid Water Electrolysis. Issue 40 (12th September 2021) - Liang, Shuaika; Jiang, Miaomiao; Luo, Hongxia; Ma, Yuanyuan; Yang, Jianping
Abstract: Water electrolysis powered by renewable energies is regarded as the most promising technology for hydrogen production. However, in conventional acid water electrolysis, the H2 production and O2 production are tightly coupled and the proton exchange membrane is required to prevent the gases mixing, which reduce the flexibility of this technology and increase its cost. Here, a low‐cost hydrated Prussian blue analog (Turnbull's blue) electrode is introduced as a solid‐state redox mediator to decouple the acid water electrolysis into two steps without the use of membrane. The redox mediator shows high‐rate performance (42.7 mAh g −1 at 120 A g −1 ) and long cycle life (5000 cycles), which is owing to the diffusion‐free Grotthuss proton conduction. Moreover, this decoupled water electrolysis device facilitates the utilization of renewable energies for high‐purity hydrogen production at different spaces and times, which shows the high flexibility for H2 production. Abstract : The low‐cost and high‐rate electrode with Grotthuss topochemistry is introduced as a solid‐state redox mediator to decouple the acid water electrolysis for hydrogen production without the use of a membrane. This decoupled water electrolysis system facilitates the utilization of renewable energies for high‐purity hydrogen production at different spaces and times, which shows the high flexibility for H2 production.